CDS and equity market reactions to stock issuances in the U.S. financial industry: Evidence from the 2002-13 period - Marcia Millon Cornett; Hamid Mehran; Kevin Pan; Minh Phan; Chenyang Wei (Federal Reserve Bank of New York, 2014)
We study market reactions to seasoned equity issuances that were announced by financial companies between 2002 and 2013. To assess the risk and valuation implications of these seasoned equity issuances, we conduct an event analysis using daily credit default swap (CDS) and stock market pricing data. The major findings of the paper are that CDS prices respond quickly to new, default-relevant information. Over the full sample period, cumulative abnormal CDS spreads drop in response to equity issuance announcements. The reactions are significantly stronger during the financial crisis. At that time, the federal government injected equity into financial institutions to ensure their viability. The market reacted to the equity issue announcements by assessing significantly lower costs for default protection via credit default swaps. The evidence indicates that single-name CDS based on financial firms' default probabilities are potentially useful for private investors and regulators.
Keywords: G01; G21; G32; 330; financial institutions; stock issuance; credit default swaps; financial crisis